SOSIALISASI PEMBUATAN E-MODUL BAGI GURU-GURU DI SMA SWASTA PERSIAPAN STABAT - Haryati; Riskyka; Yusrah; Zulham Siregar (LPPM STKIP AL MAKSUM, 2020)
The purpose of this research is to assist teachers in improving their competence and digital skills as an effort to implement digitalization of learning. The steps in this activity method are: 1) socializing and digitizing learning, 2) compiling computer-based e-module applications, 3) implementing e-module products in learning. The results of this activity show that there is a significant increase. the application of e-module media that will be used by teachers in Stabat Preparatory Private High School is very helpful for students in learning anytime and anywhere. The final results show that as the final product of making e-module media, namely e-module media products and implementation of e-module media in learning. Teachers can implement e-module products that have been made in the previous stage and are realized in learning activities.